HEALTHCARE PROVIDERS' KNOWLEDGE ON NOSOCOMIAL INFECTIONS PREVENTIVE MEASURES AND ITS ASSOCIATED FACTORS - Mohammed Ali Saleh Darraj, Sarra Saeed Break Alaklabi, Fawaz Abdullah Mohammed Alyami, Hassan Ali Ahmed Alhayli, Ahmed Abed Hassan Alayyafi, Hamad Mohammed Almansour, Waleed Saad Saeed Alghamdi, (Chelonian Research Foundation, 2023)
Background Nosocomial infections (NCIs) have been associated with several adverse outcomes including extended hospitalization, persistent disability, and heightened antimicrobial resistance, amplified socio-economic disruption, and elevated mortality rates. The adoption of infection prevention strategies has the greatest tendency to significantly reduce the risk and occurrence ofNCIs among the population, particularly in resource constrained health systems. This study aimed to assess healthcare providers ' (HCPs) knowledge on NCI preventive measures and its associated factors. Methods: A cross-sectional study was conducted in Makkah and Jeddah 's Hospital, Saudi Arabia from March to May 2023. A sample of 2371-ICPs was selected to participate in the study. Data was collected with a questionnaire designed in Google Forms. Results: Overall, most of the participants (69.2%) were not knowledgeable about the preventive measures of NCIs. HCPs who were within the age group of 20—40 years [aOR — 0.25 (95% CI — 0.09—0.69), p - 0.007] and 41-60 years [a0R = 0.05 (95% Cl = p = 0.0011 were significantly less likely to be knowledgeable about the preventive measures of NCIs compared to those who those aged less than 20 years. HCPs who attended in-service training or workshop were approximately 10 times more likely to be knowledgeable about preventive measures of nosocomi al infection compared to those who had never attended in-service training or workshop [aOR — 9.55 (95% CI = 1.23— 74.36), p = 0.0311. Conclusion: The study concludes that age and participation in-service training or workshop is significant factors that influence the knowledge of HCPs in preventive measures for nosocomial infections. These results highlight the importance of providing ongoing training and professional development opportunities to HCPs to enhance their knowledge and improve their ability to prevent and control nosocomial infections. Additionally, the study emphasizes the need for targeted training programs that consider the age ofHCPs, to ensure that training is tailored to their specific needs. Keywords: Knowledge, HCPs, Nosocomial infection, Prevention Measures.